A logical framework for net-zero climate action - Elliott, Cynthia; Schumer, Clea; Ross, Katie; Gasper, Rebecca; Singh, Neelam (Frontiers in Climate, 2023)
Momentum for national net-zero greenhouse gas (GHG) commitments is growing quickly. Nonetheless, there are justifiable concerns over their credibility. And as no country has fully decarbonized yet, it is difficult to determine whether current efforts are likely to trigger the scale of transformation required for achieving net zero. Yet it will be too late if we wait until mid-century to assess whether we have achieved this global benchmark. As nations enhance near-term action to reach their climate goals, it is critically important that we utilize stronger methods for planning and tracking real progress toward net zero. We need a framework to examine national climate action that can help hold governments accountable to their net-zero targets in real time and provide confidence to the international community that governments are making adequate efforts to radically reduce GHG emissions. This paper offers the authors' perspective on what might be an initial approach for reviewing net-zero target implementation and provides recommendations for how to qualitatively assess or evaluate national governments' net zero efforts along with suggestions for further research and study.